2021
DOI: 10.1146/annurev-biophys-090420-083836
|View full text |Cite
|
Sign up to set email alerts
|

Cutting-Edge Single-Molecule Technologies Unveil New Mechanics in Cellular Biochemistry

Abstract: Single-molecule technologies have expanded our ability to detect biological events individually, in contrast to ensemble biophysical technologies, where the result provides averaged information. Recent developments in atomic force microscopy have not only enabled us to distinguish the heterogeneous phenomena of individual molecules, but also allowed us to view up to the resolution of a single covalent bond. Similarly, optical tweezers, due to their versatility and precisions, have emerged as a potent technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…While single-molecule studies of some chaperones have also been covered in several previous reviews [18][19][20][21][22][23][24][25][26][27][28], this section provides a short description of mechanical interrogation strategies, instruments for force experiments, and our perspective on selected contributions in chaperone-client interactions that have been published since 2015. The subsections are divided into heat shock proteins, the study of the impact of chaperones on folding ribosomebound proteins, DsbA-client interactions, SNARE proteins with Mun/Munc chaperones, and chaperone-assisted folding of the membrane proteins.…”
Section: Single-molecule Mechanical Studies Of Chaperonesmentioning
confidence: 99%
“…While single-molecule studies of some chaperones have also been covered in several previous reviews [18][19][20][21][22][23][24][25][26][27][28], this section provides a short description of mechanical interrogation strategies, instruments for force experiments, and our perspective on selected contributions in chaperone-client interactions that have been published since 2015. The subsections are divided into heat shock proteins, the study of the impact of chaperones on folding ribosomebound proteins, DsbA-client interactions, SNARE proteins with Mun/Munc chaperones, and chaperone-assisted folding of the membrane proteins.…”
Section: Single-molecule Mechanical Studies Of Chaperonesmentioning
confidence: 99%
“…Single-molecule measurements give complementary information to the ensemble measurements because they can measure anisotropic properties such as force, track molecular displacements, and highlight the stochasticity of various properties, resulting in the visualization of the heterogeneity in molecular properties of different biological motors . In addition, single-molecule assays can give us information on individual steps during a multistep mechanism and the trajectories of individual molecules during a time course that is usually masked in bulk ensemble measurements. , These methods could be divided into either monitoring methods, such as single-molecule fluorescence imaging, or manipulating methods, known as single-molecule force-spectroscopy (SMFS). SMFS involves the study of the properties of individual molecules by probing them with force in the form of tension and includes techniques such as atomic force microscopy (AFM), optical tweezers (OT), and magnetic tweezers (MT) that have been widely used to divulge information on the motor properties of enzymes, mechanical unfolding pathways of proteins, as well as stabilizing effects of ligands on proteins. , Among these, optical-tweezer-based assays have championed over others in understanding the mechanisms of molecular motors, with their ability to precisely measure subnanometer displacements with microsecond temporal resolution, applying stretching forces in the range from subpiconewtons to hundreds of piconewtons. , In addition to the technical advantage of spatiotemporal resolution and range of forces the optical tweezers can measure (Table ), it gives an advantage over other methods due to its ability to steer the beads onto which molecules are attached, facilitating increased interactions between molecular motors and their substrates in the solution for faster data collection.…”
Section: Single-molecule Measurementsmentioning
confidence: 99%
“…Spatiotemporal resolutions and measurable force ranges of commonly used SMFS techniques are given in Table . ,, …”
Section: Single-molecule Measurementsmentioning
confidence: 99%
“…Protein folding under force is an important source of generating mechanical energy that harnesses different biological functions ranging from protein translation to degradation. For example, in translation, protein synthesis occurs in a confined ribosomal tunnel under 7–11 pN force, while ClpX machinery generates 4–15 pN force to unfold proteins, followed by ClpP-dependent degradation. , Notably, molecular chaperones, well involved in various folding processes, must interact with proteins under force. Recent force spectroscopy studies have nicely illustrated the molecular mechanisms of various chaperones, but most of them focused on the role of chaperones in the folding–misfolding aspects of the client proteins. ,, However, few studies reported emerging evidence that molecular chaperones could modulate the force transmission through their client polypeptide during different folding-associated processes, including during cotranslational folding at the ribosomal tunnel edge .…”
Section: Introductionmentioning
confidence: 99%